A Comparative Study for the Evaluation of Two Doses of Ellagic Acid on Hepatic Drug Metabolizing and Antioxidant Enzymes in the Rat. (18th July 2013) - Celik, Gurbet; Semiz, Aslı; Karakurt, Serdar; Arslan, Sevki; Adali, Orhan; Sen, Alaattin
Abstract : The present study was designed to evaluate different doses of ellagic acid (EA) in vivo in rats for its potential to modulate hepatic phases I, II, and antioxidant enzymes. EA (10 or 30 mg/kg/day, intragastrically) was administered for 14 consecutive days, and activity, protein, and mRNA levels were determined. Although the cytochrome P450 (CYP) 2B and CYP2E enzyme activities were decreased significantly, the activities of all other enzymes were unchanged with the 10 mg/kg/day EA. In addition, western-blot and qRT-PCR results clearly corroborated the above enzyme expressions. On the other hand, while the NAD(P)H:quinone oxidoreductase 1 (NQO1), catalase (CAT), glutathione peroxidase (GPX), and glutathione S-transferase (GST) activities were increased significantly, CYP1A, 2B, 2C, 2E, and 19 enzyme activities were reduced significantly with 30 mg/kg/day EA. In addition, CYP2B, 2C6, 2E1, and 19 protein and mRNA levels were substantially decreased by the 30 mg/kg/day dose of EA, but the CYP1A protein, and mRNA levels were not changed. CYP3A enzyme activity, protein and mRNA levels were not altered by neither 10 nor 30 mg/kg/day ellagic acid. These results indicate that EA exerts a dose-dependent impact on the metabolism of chemical carcinogens and drugs by affecting the enzymes involved in xenobiotics activation/detoxification and antioxidant pathways.